2017
DOI: 10.3324/haematol.2017.175729
|View full text |Cite
|
Sign up to set email alerts
|

Somatic STAT3 mutations in Felty syndrome: an implication for a common pathogenesis with large granular lymphocyte leukemia

Abstract: Felty syndrome is a rare disease defined by neutropenia, splenomegaly, and rheumatoid arthritis. Sometimes the differential diagnosis between Felty syndrome and large granular lymphocyte leukemia is problematic. Recently, somatic STAT3 and STAT5B mutations were discovered in 30–40% of patients with large granular lymphocyte leukemia. Herein, we aimed to study whether these mutations can also be detected in Felty syndrome, which would imply the existence of a common pathogenic mechanism between these two diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 28 publications
8
53
0
Order By: Relevance
“…From the overlapping cytokines, we found some potential biomarkers to pursue. Several studies found IL-6 and/or TRAIL were elevated in TLGLL serum/plasma samples [40, 50, 51, 54], which we also observed in the NK-LGLL patients in this study. Interestingly, all three T-LGLL studies showed IL-8 was significantly elevated in T-LGLL compared to normal donors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…From the overlapping cytokines, we found some potential biomarkers to pursue. Several studies found IL-6 and/or TRAIL were elevated in TLGLL serum/plasma samples [40, 50, 51, 54], which we also observed in the NK-LGLL patients in this study. Interestingly, all three T-LGLL studies showed IL-8 was significantly elevated in T-LGLL compared to normal donors.…”
Section: Discussionsupporting
confidence: 87%
“…BCA-1/CXCL13, EOTAXIN-2/CCL24, IP-10/CXCL10, MIG/CXCL9, MIP-3β/CCL19, MIP-1β/CCL4, SDF-1α/β/CXCL12, and XCL/Lymphotactin are all classified as chemokines with their typical function being recruitment of leukocytes [11]. Recent work by our lab and collaborators found IP-10/CXCL10 was elevated in T-LGLL vs. normal controls [50]. G-CSF/CSF-3 and GM-CSF are colony stimulating factors that typically target stem cells in the bone marrow for the purpose of granulocyte production [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current description of high LGL counts and STAT3 mutations in FS thus extends the spectrum of immune dysregulation disease conditions in which LGL cells are prominently associated (Figure 1). Notably, in their series, Savola et al found four FS cases that also showed celiac disease (CD), 4 which confirms earlier suggestions of links between LGL cells, STAT3 mutations, and CD. 13,14 The presumed common pathogenesis of LGL leukemia and immune dysregulations such as FS, CD, and bone marrow failure and related conditions (AA, hypoplastic MDS, PNH) would pave the way for more sophisticated treatment strategies than the current general immune suppressive modalities which are frequently applied.…”
supporting
confidence: 64%
“…In this issue of Haematologica they report on a cohort of 14 FS patients, which were evaluated by next-generation sequencing (NGS) technology for the occurrence of somatic mutations in the STAT3 and STAT5B genes. 4 Both of these genes have been notably implicated in a subset of the CD8 + TCRαβ + T-cell type of LGL leukemia, and the occurrence of STAT3 mutations in LGL leukemia is strongly associated with RA and neutropenia. [5][6][7] Indeed, in >40% of FS cases somatic STAT3 hotspot mutations were found, which is at a rate comparable to LGL leukemia cases.…”
mentioning
confidence: 99%